2010
DOI: 10.1111/j.1582-4934.2009.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Serially heterotransplanted human prostate tumours as an experimental model

Abstract: Preclinical research on prostate cancer (PC) therapies uses several models to represent the human disease accurately. A common model uses patient prostate tumour biopsies to develop a cell line by serially passaging and subsequent implantation, in immunodeficient mice. An alternative model is direct implantation of patient prostate tumour biopsies into immunodeficient mice, followed by serial passage in vivo. The purpose of this review is to compile data from the more than 30 years of human PC serial heterotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 100 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…Second, the fidelity with which the heterotransplant model reproduces the clinical outcome observed in patients must be characterized. This defines the predictive value of the heterotransplant model which ultimately has to predict how human beings will respond to newly developed therapies (1).…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…Second, the fidelity with which the heterotransplant model reproduces the clinical outcome observed in patients must be characterized. This defines the predictive value of the heterotransplant model which ultimately has to predict how human beings will respond to newly developed therapies (1).…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…It was shown that metabolic activity varied greatly with cell density and did not correlate in a linear fashion. High cell densities are also a feature in cancer research, where cancer cell lines are frequently used for experiments [9]. These cell lines typically proliferate rapidly and reach high cell densities over a short period of time; especially in 2D cultures [10].…”
Section: Introductionmentioning
confidence: 99%